The Contributions of Online Exit Exams in Undergraduate Programs to the Quality of Higher Education: A Systematic Review - Teshome, Samson Worku (Darul Yasin Al Sys, 2025)
This systematic review examines the role of exit examinations, particularly online exit exams in enhancing the quality of higher education, with a focus on their impact on student competency, institutional accountability, and instructional practices. Utilizing the PRISMA and PICO frameworks, the review synthesizes findings from peer-reviewed studies published over the past two decades to address the central question: How do online exit exams contribute to educational quality in higher education? The evidence indicates that when thoughtfully designed and effectively implemented, online exit exams can strengthen academic standards by aligning curriculum with intended learning outcomes, promoting institutional self-assessment, and fostering pedagogical improvement. These assessments serve as measurable indicators of student achievement and program effectiveness. However, their success is highly contingent on context, with significant challenges identified, including test-related anxiety, inequitable access to preparatory resources, and disparities among marginalized student groups. Additionally, the influence of institutional culture, technological infrastructure, and administrative support plays a critical role in determining exam efficacy. The findings suggest that a standardized, one-size-fits-all approach is insufficient; instead, a nuanced and context-sensitive implementation is essential to ensure fairness, inclusivity, and positive educational outcomes. This review calls for continued research and policy development to refine the use of online exit exams as tools for quality assurance while safeguarding equitable access and support for all learners.